Effects of bubble size on the gas–liquid mass transfer of bubble swarms with Sauter mean diameters of 0.38–4.88 mm in a co‐current upflow bubble column. Issue 11 (11th May 2020) - Wang, Zhengchao; Guo, Kai; Liu, Hui; Liu, Chunjiang; Geng, Yao; Lu, Zhe; Jiao, Boya; Chen, Dengyue
Abstract: BACKGROUND: Bubble columns have found a wide range of application in biochemical industry. Mass transfer in the bubble column can be manipulated by adjusting the bubble size. Thus, for the design of bubble columns, it is necessary to investigate the behaviors of different‐sized bubbles. This work attempts to study the global hydrodynamic and mass transfer characteristics of bubble swarms with Sauter mean diameters ( d 32 ) of 0.38–4.88 mm, from microbubbles to millimeter‐sized bubbles, in a co‐current bubble column. RESULTS: The specific interfacial areas of the bubble swarms with d 32 of 0.38–1.47 (generated by ceramic membrane module) and 1.05–4.88 mm (generated by plate gas distributor) are 250–1100 and 7–270 m −1, respectively. The liquid‐side mass transfer coefficient ( k L ) of those two kinds of bubbles are (0.45–1.16) × 10 −4 and (0.58–7.65) × 10 −4 m s −1, respectively. CONCLUSION: Decreasing the bubble size can effectively increase the volumetric mass transfer coefficient ( k L a ), especially when the bubble size decreases to several micrometers. The major contribution to the mass transfer enhancement results from the increase of the specific interfacial area. Conversely, the k L decreases clearly. It is demonstrated that Higbieʼs and Frosslingʼs equations can approximate the k L of the bubble swarms with d 32 > 2 mm and d 32 < 2 mm in the bubble column, respectively. © 2020 Society of Chemical Industry